Alternative Dispute Resolution For Electronic Commerce Transactions - R.S. Gopal, G. Premman (2004)
Disputing parties in E-Commerce transactions would try to resolve disputes as soon as possible instead of allowing third party intervention such as lawyers. It is becoming a growing trend for corporate entities to evaluate risks and develop alternative methods for early dispute resolution. This thesis by way of literature review examines the applicability of alternative dispute resolution to E-Commerce transactions.